(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2023)
Background: Decreased endurance of trunk extensors is a significant risk factor for Low Back Pain (LBP). Clinicians treating low back pain often use exercise to reduce pain and improve function. This study evaluated the effectiveness of supervised trunk extensor endurance training in reducing pain and decreasing disability in subjects with chronic LBP. Materials and methods: This clinical trial included 92 patients with chronic LBP from the department of Physical Medicine & Rehabilitation, Chittagong Medical College Hospital, from July to December 2017. Patients were randomly assigned to either an experimental group (n=46) or a control group (n=46). Subjects in the experimental group attended supervised trunk endurance exercise sessions three times weekly for six weeks, but subjects in the control group performed exercises at home without supervision. A Visual Analogue Scale (VAS) for pain assessment and Sorensen Test was used to measure trunk extensor endurance. Reassessments were carried out at 3 and 6 weeks. Results: Mean scores of the Sorensen test in the initial, 2nd & 3rd visits were 122.1±22.2, 127.0±13.5 & 126.6±18.5 respectively, in the experimental group, which were 123.2±8.2, 121.4±6.9 & 122.0±5.5 in the control group. There was no statistical difference (p>0.05) in 1st & the 2nd visit, while 2nd & the 3rd week significantly improved in the experimental group than the control group (p<0.05). The mean score of VAS was 4.07±1.70, 2.87±1.34 & 2.11±1.23 in the 1st, 2nd & 3rd visits, respectively, in group A. But in Group B which were 4.48±1, 3.59±1 & 3.54±1.35.02 in 1st, 2nd & 3rd visit respectively. The pain was significantly decreased in the experimental group after the 2nd and 3rd visits compared to the control group (p=<0.001). A negative correlation was found between the VAS and Sorensen test in every visit in both groups, indicating that improved back extensors’ endurance resulted in decreased pain. Conclusion: This study demonstrated the beneficial effect of supervised trunk extensors endurance exercise on chronic LBP, reducing pain and increasing endurance. JCMCTA 2023 ; 34 (1) : 47-51